Case Study on Market Mix Strategies of Toyota Motor Corporation - Madoh, Abdullah; Alenazi, Jumana; Alkhamees, Lulwa; Panwar, Abhilash (AIBPM Publisher, 2019)
Toyota Motor Corporation is a Japanese multinational automotive manufacturer headquartered in Toyota City, Aichi, Japan. In 2017, Toyota's corporate structure consisted of 364,445 employees worldwide and, as of September 2018, was the sixth-largest company in the world by revenue. As of 2017, Toyota is the world's second-largest automotive manufacturer. Toyota was the world's first automobile manufacturer to produce more than 10 million vehicles per year which it has done since 2012, when it also reported the production of its 200-millionth vehicle. As of July 2014, Toyota was the largest listed company in Japan by market capitalization and by revenue. Toyota is the world's market leader in sales of hybrid electric vehicles, and one of the largest companies to encourage the mass-market adoption of hybrid vehicles across the globe. Toyota is also a market leader in hydrogen fuel-cell vehicles. Cumulative global sales of Toyota and Lexus hybrid passenger car models achieved the 10 million milestones in January 2017. Its Prius family is the world's top selling hybrid nameplate with over 6 million units sold worldwide as of January 2017.